Modelling of gapless zinc-oxide surge arrester using p-spice - 443045 Mohd. Junaidi Abdul Aziz (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2000